KESESUAIAN ENERGI “QI” DARI MODIFIKASI BANGUNAN ALIH FUNGSI PADA MASJID AL IMTIZAJ, BANDUNG - Nindya Caesa Azuhra; Herman Wilianto (Riset Arsitektur (RISA), 2022)
Abstract - Al-Imtizaj Mosque in Bandung has a Chinese-Islamic acculturated building design. By using the old and modified building, it can change the function of the building, that is what the Al Imtizaj Mosque does. Changing the function of the building, there is a change in the element of Qi energy which according to Feng Shui is very important for the welfare of the building and building users. How can these building modifications create or produce appropriate "Qi" energy for places of worship based on the Feng Shui Theory of the flow of forms and the five elements? This study aims to determine the suitability of Qi energy resulting from the modification of the Al Imtizaj building according to Feng Shui Theory for worship buildings. As well as providing benefits so that the Al Imtizaj Bandung mosque building can be used as a cultural heritage building with cultural preservation. The research method used is descriptive exploratory where this study describes and assesses objects that are supported by existing literature data. Keywords: Fengshui, Qi Energi, Mosque, Islamic Architecture, At Al Imtizaj Mosque Bandung